2023
DOI: 10.1103/physrevd.107.024014
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear studies of binary black hole mergers in Einstein-scalar-Gauss-Bonnet gravity

Abstract: Gravitational wave observations of black hole-neutron star binaries, particularly those where the black hole has a lower mass compared to other observed systems, have the potential to place strong constraints on modifications to general relativity that arise at small curvature length scales. Here we study the dynamics of black hole-neutron star mergers in shift-symmetric Einstein-scalar-Gauss-Bonnet gravity, a representative example of such a theory, by numerically evolving the full equations of motion. We con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 162 publications
0
2
0
Order By: Relevance
“…Clearly, the most sensitive and accurate test would be performed using coherent IMR models in specific alternative scenarios. Recent progress has been made in constructing such models, both analytically and numerically [136][137][138][139][140]. However, the large classes of possible deviations from GR makes this a daunting task, and naturally calls for generic models and parameterisations [141][142][143][144][145][146][147][148] capable of capturing deviations from several classes of modifications.…”
Section: Ringdown Modelsmentioning
confidence: 99%
“…Clearly, the most sensitive and accurate test would be performed using coherent IMR models in specific alternative scenarios. Recent progress has been made in constructing such models, both analytically and numerically [136][137][138][139][140]. However, the large classes of possible deviations from GR makes this a daunting task, and naturally calls for generic models and parameterisations [141][142][143][144][145][146][147][148] capable of capturing deviations from several classes of modifications.…”
Section: Ringdown Modelsmentioning
confidence: 99%
“…This requires a well-posed initial-value formulation of the equations of motion that is amenable to numerical simulations. Finding such a formulation is a significant challenge in many settings beyond GR, that has only partially been met in a small subset of theories [78][79][80][81]. In contrast, to compare a spacetime beyond Kerr to VLBI data, one does not even need to know which dynamics that spacetime is a solution to.…”
Section: Jcap05(2024)103mentioning
confidence: 99%
“…There is at least one private code, based on the PAMR/AMRD and HAD (East et al, 2012;Neilsen et al, 2007) infrastructure, that was used in the first works to successfully implement the modified general harmonic gauge for 4𝜕ST (Corman et al, 2023;East & Pretorius, 2022;East & Ripley, 2021b, 2021a. Since this code uses a Generalised Harmonic Coordinates (GHC) formulation, it necessitates excision of the interior of black holes, which can be difficult to implement in practice.…”
Section: Statement Of Needmentioning
confidence: 99%
“…An important breakthrough was made in 2020 by Kov'acs and Reall, who showed that Horndeski theories are indeed well-posed in a modified version of the harmonic gauge (Kovács & Reall, 2020b) -a particular coordinate system already used in NR. Subsequently, several specific theories within these classes were probed in their highly dynamical and fully non-linear regimes (Corman et al, 2023;East & Pretorius, 2022;East & Ripley, 2021b, 2021a. The extension of the results of (Kovács & Reall, 2020b to the alternative "singularity avoiding" coordinates in (Aresté Saló et al, 2022Doneva et al, 2023) offers an alternative gauge in which to probe questions of hyperbolicity, and may offer stability advantages for certain cases such as unequal mass ratios, as studied in (Corman et al, 2023).…”
mentioning
confidence: 99%
See 1 more Smart Citation